Politik Hukum Pemulihan Ekonomi Nasional Akibat Pandemi Covid-19 Perspektif Konstitusi Ekonomi - Lutfi, Mustafa; Supriyadi, Aditya Prastian (De Jure: Jurnal Hukum dan Syari'ah, 2021)
Abstract :The Covid-19 pandemic has slowed the pace of economic growth in Indonesia. As a result, several business sectors in the community experienced a decline, so the state issued a legal policy to take steps to resolve it. Legal politics as a form of government policy in an effort to restore the national economy is a necessity. This article uses a type of normative juridical research method, with a statutory and conceptual approach, legal materials (primary, secondary, tertiary) are analyzed using the content analysis method. This article shows and emphasizes the urgency of the government's legal politics in efforts to recover the national economy due to the Covid-19 pandemic. In the process of its formation, it certainly requires a comprehensive, integrated and targeted policy set. The 1945 Constitution Article 22 paragraphs (1-3) provides space for the government to stipulate Perpu No. 1 of 2020 becomes Law No. 2 of 2020 as a legal umbrella in an effort to maintain the resilience of all elements of the nation from all threats that endanger the safety of the people of the nation and state. The role of the government's legal policy in national economic recovery has a central position in anticipating a fragile "system" and management. The national economic recovery policy cannot be separated from the legal politics policy itself, of course by taking into account the principles of prudence, good faith and full integrity and remains based on the principles of good governance, accountability, and transparency.Keyword: Legal Politics, Economic Recovery, Covid-19, Economic Constitution.Abstrak :Pandemi Covid-19 memperlambat laju pertumbuhan ekonomi di Indonesia. Akibatnya beberapa sektor usaha bisnis di masyarakat mengalami penurunan, sehingga negara mengeluarkan kebijakan hukum untuk mengambil langkah penyelesaian. Politik hukum sebagai bentuk kebijakan pemerintah dalam upaya pemulihan ekonomi nasional menjadi keniscayaan. Artikel ini menggunakan jenis metode penelitian yuridis normatif, dengan pendekatan perundang-undangan dan konseptual, bahan hukum (primer, sekunder, tersier) dianalisis menggunakan metode content analysis. Artikel ini menunjukan dan menekankan urgensi politik hukum pemerintah dalam upaya pemulihan ekonomi nasional akibat pandemi Covid-19. Dalam proses pembentukannya tentu membutuhkan perangkat kebijakan yang komprehensif, terintegrasi dan tepat sasaran. Konstitusi UUD 1945 Pasal 22 ayat (1-3) memberikan ruang bagi pemerintah menetapkan Perpu No. 1 Tahun 2020 menjadi UU No. 2 Tahun 2020 sebagai payung hukum dalam upaya dan menjaga ketahanan seluruh elemen bangsa dari segala ancaman yang membahayakan keselamatan masyarakat bangsa dan negara. Peran kebijakan hukum pemerintah dalam pemulihan ekonomi nasional, memiliki kedudukan sentral guna mengantisipasi â€œsistemâ€ dan manajeman yang rapuh. Kebijakan pemulihan ekonomi nasional tidak lepas dari kebijakan politik hukum itu sendiri, tentu dengan memperhatikan prinsip-prinsip kehati-hatian, itikad baik dan penuh integritas serta tetap berlandaskan pada asas tata kelola yang baik, akuntabilitas, dan transparansi.Kata Kunci : Politik Hukum, Pemulihan Ekonomi, Covid-19, Konstitusi Ekonomi.Abdullah, Irwan. â€œCOVID-19: Threat and Fear in Indonesia.â€ Psychological Trauma: Theory, Research, Practice, and Policy 12, no. 5 (July 2020): 488â€“90. https://doi.org/10.1037/tra0000878.Adhe, Kartika Rinakit, Rohmatul Maulidiya, Muchamad Arif Al Ardha, Wulan Patria Saroinsong, and Sri Widayati. â€œLearning During the Covid-19 Pandemic: Correlation Between Income Levels And Parental Roles.â€ Jurnal Obsesiâ€¯: Jurnal Pendidikan Anak Usia Dini 5, no. 1 (June 8, 2020): 293-302â€“302. https://doi.org/10.31004/obsesi.v5i1.554.Ali, Imran, and Omar M. L. Alharbi. â€œCOVID-19: Disease, Management, Treatment, and Social Impact.â€ The Science of the Total Environment 728 (August 1, 2020): 138861. https://doi.org/10.1016/j.scitotenv.2020.138861.Altig, Dave, Scott Baker, Jose Maria Barrero, Nicholas Bloom, Philip Bunn, Scarlet Chen, Steven J. Davis, et al. â€œEconomic Uncertainty before and during the COVID-19 Pandemic.â€ Journal of Public Economics 191 (November 1, 2020): 104274. https://doi.org/10.1016/j.jpubeco.2020.104274.Asshiddiqie, Jimly. â€œMemperkenalkan Gagasan Konstitusi Ekonomi.â€ Jurnal Hukum PRIORIS 3, no. 2 (May 17, 2016): 1â€“26.Astomo, Putera. â€œPembentukan Undang-Undang dalam Rangka Pembaharuan Hukum Nasional Di Era Demokrasi.â€ Jurnal Konstitusi 11, no. 3 (May 20, 2016): 577â€“99. https://doi.org/10.31078/jk%x.Bhuiyan, A. K. M. Israfil, Najmuj Sakib, Amir H. Pakpour, Mark D. Griffiths, and Mohammed A. Mamun. â€œCOVID-19-Related Suicides in Bangladesh Due to Lockdown and Economic Factors: Case Study Evidence from Media Reports.â€ International Journal of Mental Health and Addiction, May 15, 2020, 1â€“6. https://doi.org/10.1007/s11469-020-00307-y.Bonal, Xavier, and Sheila GonzÃ¡lez. â€œThe Impact of Lockdown on the Learning Gap: Family and School Divisions in Times of Crisis.â€ International Review of Education, September 15, 2020. https://doi.org/10.1007/s11159-020-09860-z.Burhanuddin, Chairul Ihsan, and Muhammad Nur Abdi. â€œKRISIS EKONOMI GLOBAL DARI DAMPAK PENYEBARAN VIRUS CORONA (COVID-19).â€ AkMen JURNAL ILMIAH 17, no. 1 (March 31, 2020): 90â€“98.Chapra, M. Umer. Islam and the Economic Challenge. Leicester: Islamic Foundation, 2003.Coccia, Mario. â€œThe Relation between Length of Lockdown, Numbers of Infected People and Deaths of Covid-19, and Economic Growth of Countries: Lessons Learned to Cope with Future Pandemics Similar to Covid-19 and to Constrain the Deterioration of Economic System.â€ The Science of the Total Environment 775 (June 25, 2021): 145801. https://doi.org/10.1016/j.scitotenv.2021.145801.Dewantara, Reka, and Dien Nufitasari. â€œPOLITIK HUKUM PENGATURAN MENGENAI TINDAKAN PENCEGAHAN NON PERFORMING LOAN PADA BANK DALAM MASA PANDEMIK DENGAN PENDEKATAN KONSEP BIFURKASI HUKUM.â€ Jurnal Bina Mulia Hukum 6, no. 1 (September 30, 2021): 66â€“83. https://doi.org/10.23920/jbmh.v6i1.176.Fitria, Tira Nur. â€œKontribusi Ekonomi Islam Dalam Pembangunan Ekonomi Nasional.â€ Jurnal Ilmiah Ekonomi Islam 2, no. 03 (November 19, 2016). https://doi.org/10.29040/jiei.v2i03.3.Friedman, Lawrence M. Hukum Amerika: Sebuah Pengantar. Translated by Wisnu Basuki. Jakarta: PT. Tatanusa, 2001. http://books.google.com/books?id=0Bg7AQAAIAAJ.Gupta, Anubhab, Heng Zhu, Miki Khanh Doan, Aleksandr Michuda, and Binoy Majumder. â€œEconomic Impacts of the COVIDâˆ’19 Lockdown in a Remittance-Dependent Region.â€ American Journal of Agricultural Economics 103, no. 2 (2021): 466â€“85. https://doi.org/10.1111/ajae.12178.Hermanto, Asep Bambang. â€œPandangan Tentang Apakah Politik Hukum Itu?â€ Jurnal Hukum dan Bisnis (Selisik) 5, no. 2 (December 31, 2019): 31â€“43. https://doi.org/10.35814/selisik.v5i2.1687.Indaryanto, Wisnu. â€œDAMPAK PANDEMI COVID-19 DAN URGENSI PEMBENTUKAN PERATURAN DAERAH TENTANG BANTUAN HUKUM.â€ Jurnal Legislasi Indonesia 18, no. 3 (September 30, 2021): 309â€“23. https://doi.org/10.54629/jli.v18i3.777.â€œIndonesia: Expanding Access to Islamic Finance for SMEs.â€ Accessed December 31, 2021. https://www.firstinitiative.org/stories/indonesia-expanding-access-islamic-finance-smes.KAHF, Monzer. Ekonomi Islamâ€¯: Telaah Analitik Terhadap Fungsi Sistem Ekonomi Islam. Yogyakarta: Pustaka Pelajar, 1995.Kurniawan, Muhamad Beni. â€œPolitik Hukum Pemerintah dalam Penanganan Pandemi Covid-19 Ditinjau dari Perspektif Hak Asasi atas Kesehatan.â€ Jurnal HAM 12, no. 1 (April 22, 2021): 37â€“56. https://doi.org/10.30641/ham.2021.12.37-56.Mahfud MD", Moh. Membangun politik hukum, menegakkan konstitusi. Jakarta: Rajawali Pers, 2010.Masoed, Mochtar. Ekonomi-politik internasional dan pembangunan. Yogyakarta: Pustaka Pelajar, 1994.MD, Mahfud, and Abdul Gani. â€œMembangun Politik Menegakkan Konstitusi.â€ In Membangun Politik Hukum, Menegakkan Konstitusi. Jakarta: Konstitusi Press, 2012.Mikhael, Lefri. â€œCovid-19 Vaccination as Part of The Basic Right to Health, Should It Be Mandatory During The Covid-19 Pandemic.â€ SASI 27, no. 4 (November 27, 2021): 423â€“29. https://doi.org/10.47268/sasi.v27i4.682.Otoritas Jasa Keuangan. â€œSyariah.â€ Accessed December 31, 2021. https://www.ojk.go.id/id/kanal/syariah/Pages/Perbankan-Syariah.aspx.Radjagukguk, Erman. Peranan Hukum Dalam Pembangunan Pada Era Globalisasiâ€¯: Implikasinya Bagi Pendidikan Hukum Di Indonesia. Jakarta: UI Press, 1997. http://lib.ui.ac.id.Rahardjo, Satjipto. Ilmu Hukum. Bandung: Citra Aditya Bakti, 2013.â€œResesi Ekonomi Indonesia: Pemerintah Disarankan Fokus â€˜menangani Pandemiâ€™ Demi Perbaikan Ekonomi - BBC News Indonesia.â€ Accessed December 31, 2021. https://www.bbc.com/indonesia/indonesia-53152994.Sadeq, AbulHasan Muhammad. Development Issues in Islam. Kuala Lumpur: Research Centre IIUM, 2006.Santoso, Yusuf Imam. â€œIni Delapan Dampak Negatif Bagi Perekonomian Indonesia Akibat Wabah Virus Corona.â€ Accessed December 31, 2021. https://nasional.kontan.co.id/news/ini-delapan-dampak-negatif-bagi-perekonomian-indonesia-akibat-wabah-virus-corona.Satria, Adhi Putra. â€œSibernetika Talcott Parsons: Suatu Analisis Terhadap Pelaksanaan Omnibus Law Dalam Pembentukan Undang-Undang Cipta Lapangan Kerja Di Indonesia.â€ Indonesian State Law Review (ISLRev) 2, no. 2 (May 28, 2020): 111â€“18. https://doi.org/10.15294/islrev.v2i2.37317.Sen, Amartya Kumar. Beyond the Crisis: Development Strategies in Asia. Singapore: Institute of Southeast Asian Studies, 2000.Silva Neto, Raimundo Monteiro da, Cicero Jonas Rodrigues Benjamim, Poliana Moreira de Medeiros Carvalho, and Modesto Leite Rolim Neto. â€œPsychological Effects Caused by the COVID-19 Pandemic in Health Professionals: A Systematic Review with Meta-Analysis.â€ Progress in Neuro-Psychopharmacology Biological Psychiatry 104 (January 10, 2021): 110062. https://doi.org/10.1016/j.pnpbp.2020.110062.Simanjuntak, Rico Afrido. â€œPemerintah Tak Ingin Tiru Italia Dan India Gagal Dengan Lockdown.â€ Accessed December 31, 2021. https://nasional.sindonews.com/berita/1575424/15/pemerintah-tak-ingin-tiru-italia-dan-india-gagal-dengan-lockdown.Soemitro, Ronny Hanitijo. Perspektif Sosial Dalam Pemahaman Masalah-Masalah Hukum. Semarang: CV. Agung, 1989.Sudirman, Sudirman, Ramadhita Ramadhita, Syabbul Bachri, Erfaniah Zuhriah, and Zaenul Mahmudi. â€œThe Family Corner for the Post-COVID 19 Revitalization of Family Function.â€ Samarah: Jurnal Hukum Keluarga Dan Hukum Islam 5, no. 1 (June 30, 2021): 88â€“107. https://doi.org/10.22373/sjhk.v5i1.9122.Sugianto, Danang. â€œSeberapa Dahsyat Efek Corona Ke Ekonomi RI?â€ Accessed December 31, 2021. https://finance.detik.com/berita-ekonomi-bisnis/d-5055905/seberapa-dahsyat-efek-corona-ke-ekonomi-ri.Vago, Steven, and Steven E Barkan. Law and Society. Milton: Taylor Francis Group, 2021. http://public.eblib.com/choice/PublicFullRecord.aspx?p=6507082.Wang, Chunlei, Dake Wang, Jaffar Abbas, Kaifeng Duan, and Riaqa Mubeen. â€œGlobal Financial Crisis, Smart Lockdown Strategies, and the COVID-19 Spillover Impacts: A Global Perspective Implications From Southeast Asia.â€ Frontiers in Psychiatry 12 (2021): 1099. https://doi.org/10.3389/fpsyt.2021.643783.Wildan, Muhammad. â€œPertumbuhan Ekonomi Global Diprediksi -2,2 Persen Bagaimana Dampaknya Ke RI?â€ Accessed December 31, 2021. https://ekonomi.bisnis.com/read/20200414/9/1226850/pertumbuhan-ekonomi-global-diprediksi-22-persen-bagaimana-dampaknya-ke-ri.Zuraya, Nidia. â€œTiga Dampak Besar Pandemi Covid-19 Bagi Ekonomi RI | Republika Online.â€ Accessed December 31, 2021. https://republika.co.id/berita/qdgt5p383/tiga-dampak-besar-pandemi-covid-19-bagiekonomi-ri.